Penerapan Model Discovery Learning Berbantuan Media Canva Untuk Meningkatkan Motivasi Siswa Pada Pembelajaran Menulis Surat Pribadi - Neng Tuti Novianty; Diena San Fauziya (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to determine the application of the discovery learning model assisted by canva media in increasing student motivation in learning to write personal letters. The research method used was a quantitative – experimental approach with a pre-experimental design in the form of one group pretest-posttest which was tested twice: first before treatment (pretest) and second after treatment (posttest). The sample in this study was 35 class VII students of SMP Negeri 1 Parongpong for the 2023/2024 academic year who were selected using a purposive sampling technique. The results of the research show that there is an increase in students' motivation in learning to write personal letters by applying the discovery learning model assisted by Canva media, with the average score before treatment being 59.89 and after treatment being 80.00 with a significance value of 0.000 < 0.05. Therefore, it can be concluded that the use of the discovery learning model assisted by Canva media is effective in increasing student motivation in learning to write personal letters.